International Migration: Perspectives from Origin and Host Countries (Journal of Population and Development, 2022)
This paper attempts to describe the trends as well as opportunities and challenges of international migration from the side of both origin and host countries. International migration and remittances are being important as well as debatable issues in current context. Secondary sources of data and information are used in this paper. The opportunities and challenges are analyzed from both sending and host countries. There is no unanimous views among the scholars about opportunities and challenges of migrants in the context of sending and host countries. Remittances have been contributed to reduce poverty level of migrants’ households and migration has been contributed to replace the ageing work force of the developed countries. The decreasing working age population due to decreased fertility rate in the context of economically developed countries has been a major policy concern.